Digital Storytelling in English Language Teaching (ELT) Engaging Learners Through Multimedia Narratives - Fitria, Tira Nur; Afdaleni, Afdaleni (STKIP PGRI Ponorogo Press, 2025)
This research describes the digital storytelling in ELT in engaging learners through multimedia narratives. This research is library research. The analysis shows that storytelling is a traditional method of conveying experiences, ideas, and emotions through words, images, and sound. It involves narrating stories that share personal experiences and facilitate emotional connections between individuals. In education, storytelling enriches learning by presenting vivid narratives that convey values, morals, and knowledge effectively. In ELT specifically, storytelling aids in understanding language structures, improving speaking skills, and deepening comprehension of target language cultures. Digital storytelling in ELT encompasses various applications that enhance language learning through multimedia narratives. Students engage in personal narrative projects, book reviews in video format, and historical or cultural storytelling to develop English proficiency and critical thinking. They use digital storyboards to structure narratives, interactive apps for creative storytelling, and collaborate on digital projects to foster teamwork. Competitions and augmented reality (AR) applications further motivate students, promoting language skills, cultural awareness, and digital literacy in dynamic educational settings. Digital storytelling in ELT relies on various platforms, tools, and resources for creating and engaging with multimedia narratives. It integrates images, videos, and audio to deepen reflection and articulate personal or academic content creatively. Educators access curated materials from sources like the British Council's Teaching English and TESOL International, while educational apps and YouTube offer templates and examples for language learners. Besides, professional journals, webinars, and teacher networks provide further support, promoting effective implementation of digital storytelling to enhance learning and collaboration in ELT classrooms.